Study on factors determining employee receptivitiy to organizational change and the flexible wage system. - Lam, Xiao Jie. (2008)
This study explores the significant relationships of organizational factors, specifically organizational commitment and perceived organizational support, on employee's receptivity towards a flexible wage system and openness towards an organizational change. Effects of individual factors, consisting job involvement and career commitment on employee's openness towards an organizational change are also examined.